The Comparative Method in the Study of Religion and Race: a Reflection on Lincoln and Freiberger - Prentiss, Craig R. (Method & theory in the study of religion, 2020)
This essay compares Bruce Lincoln’s Apples and Oranges with Oliver Freiberger’s Considering Comparison and applies lessons derived from these works to my own research in the fields of religion and race. Attention to both authors’ concerns with the relationship between definitions and theories, as well as positionality and scope, result in my confusion as to whether the categories of “religion” and “race” can be profitably compared without being trapped in a world of tautology. Yet their shared emphases on comparison as a heuristic enterprise may open a path for making useful claims in this area of research by means of comparative method.